PEMBERDAYAAN EKONOMI MASYARAKAT BERBASIS MASJID DI PONTIANAK - Ruslan, Ismail (Khatulistiwa, 2012)
In reality, the growth of mosques and surau (smaller mosques) in the city of Pontianak is fast, like mushrooms in the rainy season. The data from the Ministry of Religious Affairs of Pontianak in 2008 shows that the number of mosques and surau was 336 in total. However, the number was not accompanied with activities for economic development of the Muslim society. Similarly, in terms of the number, the majority of people in the city of Pontianak is Muslim, and certainly this has the potential for the empowerment, both in terms of human resources and natural resources (including the Muslim funds). This subject is necessary to be studied by considering: first, the economic conditions of the communities in the city of Pontianak lie under the poverty line and the economic underdevelopment. Therefore, it requires a real effort to improve their economic condition. Second, this article is as an effort to re-actualize the role and functions of mosques as well as the shifting paradigm of the Muslim community in the city of Pontianak regarding the mosque.